2013
DOI: 10.1080/10627197.2013.761527
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting Domains of Assessment Knowledge: School Typologies Based on Interviews with Secondary Teachers

Abstract: This study used qualitative interviewing with teachers at three high schools to answer research questions about teachers' assessment knowledge, school-specific assessment cultures, and teachers' perceptions of the assessment literacy of other key stakeholders. Data analysis revealed shared knowledge and practices across schools-use of formative assessment to guide instructional decision making; reliance on collaborative processes as the basis for cultivating school-wide assessment practices; and the belief amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…The more favorable attitude toward assessment shown by inservice teachers is interesting and somewhat contradictory to the findings of Quilter and Gallini (2000) and Howley et al (2013) discussed earlier which found that teachers did not always have a positive view of assessment practices and formative practices in particular.…”
Section: Preservice Teachers' Assessment Literacycontrasting
confidence: 96%
See 4 more Smart Citations
“…The more favorable attitude toward assessment shown by inservice teachers is interesting and somewhat contradictory to the findings of Quilter and Gallini (2000) and Howley et al (2013) discussed earlier which found that teachers did not always have a positive view of assessment practices and formative practices in particular.…”
Section: Preservice Teachers' Assessment Literacycontrasting
confidence: 96%
“…It is very common for studies to display the low levels of assessment literacy among preservice and inservice teachers, but it is not as common for them to dig into the specifics of where and why assessment literacy is low (Howley, Howley, Henning, Gillam, & Weade, 2013).…”
Section: Significance Of the Studymentioning
confidence: 99%
See 3 more Smart Citations